THE INFLUENCE OF OWNERSHIP CONCENTRATION ON THE DIVIDEND POLICY OF RUSSIAN COMPANIES - E. A. Fedorova; A. B. Voronkevich; C. A. Kameneva (Финансы: теория и практика, 2017)
The structure and concentration of ownership as one of the corporate governance mechanisms influence on decision-making process about dividends. The impact of the share capital structure for the payment or non-payment of dividends is important as owners under Russian corporate law ultimately affect the availability and amount of payments by making decisions at the meeting. The aim of the research is to evaluate the effect of an equity structure on the dividend policy of Russian public companies by means of economic and mathematical modeling techniques, exactly by the method of constructing a standard logistic regression model. The resulting model is formed on the basis of data about companies, representing 9 industries: mining, industry, electricity and gas supplies, construction, wholesale and retail trade, transport, agriculture, real estate and telecommunications. The research confirms the hypothesis, which suggest a relationship between the presence of the owner on the manager position and the fact of. Hypotheses about the impact the presence of the state, financial and non-financial institution in the structure of the share capital on dividend payments have not been confirmed and shown an inverse relationship. Effect of non-financial companies on the dividends turned out to be insignificant for the given model. Results of the study will allow managers, shareholders, potential investors and other stakeholders to monitor the company’s current situation and forecast the effects of corporate governance impact on its dividend policy.